Distribution of trace elements in edible green seaweed (Caulerpa Taxifolia) in Langkawi - Shamsuddin, Masayu; Mohamed Rehan, Aisyah; Kamarudin, Kamarul Rahim (2008)
Seaweeds or marine algae belong to a group of marine plants. It has been used for food and medicine in many communities worldwide due to its beneficial substances. In marine environment, heavy metals may occur as dissolved free metal ions that can be incorporated into the algae’s skeletal structures. Since many heavy metals are very toxic and can threaten the health of organisms, this study aims to investigate the elemental distribution in a local edible green seaweed species, Caulerpa taxifolia (‘latok lipan’) consumed by local Langkawi residents. The seaweed was collected from Sungai Kilim, an area of brackish water in Langkawi island coastline. The dried samples of C. taxifolia were digested using trace metal HNO3 overnight and diluted with deionized water (1:5).The results were compared with the seawater sample collected in the sampling area in Sungai Kilim. The seawater sample were purified and acidified before treated with methyl isobutyl ketone (MIBK) solution and 1% ammonium pyrrolidine dithiocarbamate (APDC) solution. Four elements; Cadmium (Cd), Ferum (Fe), Chromium (Cr) and Copper (Zn) present in both the seaweed and the seawater samples were determined using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). The results showed a very significant level of heavy metal in the C. taxifolia samples analysed; with Cr concentration at 5.016 μg/L, followed by Cu (1.870 μg/L), Fe (1.626 μg/L) and Cd (0.236 μg/L). The seawater sample was found to have lower concentrations of heavy metal tested, ranging from 0.024 μg/L for Cd to 1.262 μg/L for Fe. These preliminary findings indicated the need for cautionary use of C. taxifolia for human consumption as well as its potential application as a bioindicator for metal pollution studies in Sungai Kilim. Further study will need to be be performed to verify and compare the level of heavy metal elements analysed and to investigate any possible heavy metal contamination in the samples.